Isolation and Screening of Soil Chitinolytic Actinobacteria as the Anti-Fungal Producer of Plant Pathogens - Risky Hadi Wibowo; Sipriyadi Sipriyadi; Nisa Rachmania Mubarik; Iman Rusmana; Maggy Thenawidjaya Suhartono (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2020)
Abstract: Chitinolytic actinobacteria are currently more widely used because of their ability as the biological control agents to the pathogenic fungi, especially in horticultural and plantation crops. This research was conducted to obtain isolates of chitinolytic soil actinobacteria from the rhizosphere of the rubber plant (Hevea brasiliensis) area in IPB University. Antifungal activities from these actinobacteria hopely able to inhibit the growth of plant pathogenic fungi in Vitro on chitin agar media. Fusarium oxysporum and Sclerotium rolfsii are used in the inhibition test of chitinolytic actinobacteria. The results successfully obtained 16 isolates of actinobacteria were grew on Humic Acid Vitamin (HV) agar. It showed that six of 16 actinobacteria isolates were able to produce inhibition zones to the growth of hyphae of pathogenic fungi on potato dextrose agar (PDA). KK-15 and KK-07 isolates were able to produce the largest inhibition percentages in F. oxysporum and S. rolfsii. Based on the chitinolytic index (CI) values, KK-15 and KK-07 isolates produced CI values of 1.25 and 1.5, respectively. The morphological characteristics and Gram staining of both KK-15 and KK-07 isolates are closely relative with Streptomyces sp. Abstrak: Bakteri kitinolitik saat ini banyak diteliti karena kemampuannya sebagai agens pengendali hayati jamur patogen khususnya pada tanaman hortikultura dan perkebunan. Penelitian ini dilakukan untuk mendapatkan isolat-isolat bakteri kitinolitik asal tanah dari bagian perakaran tanaman karet (Hevea brasiliensis) di daerah perkebunan karet Institut Pertanian Bogor (IPB). Aktivitas antifungi dari bakteri ini diharapkan mampu menghambat pertumbuhan jamur patogen tanaman secara in Vitro pada media agar-agar kitin. Fusarium oxysporum dan Sclerotium rolfsii digunakan dalam uji hambat aktinobakteri kitinolitik. Hasil penelitian memperoleh 16 isolat aktinobakteri berhasil diisolasi dengan menggunakan media agar-agar Humic Acid Vitamin (HV), dan dari 16 isolat tersebut, enam isolat mampu menghasilkan zona hambat terhadap pertumbuhan hifa dari kedua jamur patogen pada media Potato Dextrose Agar (PDA) secara in Vitro. Isolat KK-15 dan KK-07 mampu menghasilkan diameter hambatan terbesar pada jamur F. oxysporum dan S. rolfsii. Berdasarkan nilai index kitinolitik (IK), isolat KK-15 dan KK-07 menghasilkan nilai IK sebesar 1,25 dan 1,5 secara berurutan. Karakteristik morfologi dan pewarnaan Gram dari kedua isolat yaitu KK-15 dan KK-07 memiliki kedekatan dengan kelompok Streptomyces spp.